The role of floods and droughts on riverine ecosystems under a changing climate - Piotr Parasiewicz; Elise L. King; J. Angus Webb; Mikołaj Piniewski; Claudio Comoglio; Christian Wolter; Anthonie D. Buijse; David Bjerklie; Paolo Vezza; Andreas Melcher; Katarzyna Suska (Fisheries Management and Ecology, 2019)
Floods and droughts are key driving forces shaping aquatic ecosystems. Climate change may alter key attributes of these events and consequently health and distribution of aquatic species. Improved knowledge of biological responses to different types of floods and droughts in rivers should allow the better prediction of the ecological consequences of climate change‐induced flow alterations. This review highlights that in unmodified ecosystems, the intensity and direction of biological impacts of floods and droughts vary, but the overall consequence is an increase in biological diversity and ecosystem health. To predict the impact of climate change, metrics that allow the quantitative linking of physical disturbance attributes to the directions and intensities of biological impacts are needed. The link between habitat change and the character of biological response is provided by the frequency of occurrence of the river wave characteristic—that is the event's predictability. The severity of impacts of floods is largely related to the river wave amplitude (flood magnitude), while the impact of droughts is related to river wavelength (drought duration).